EMPOWERMENT OF FEMALE EMPING ARTISANS: OBSTACLES AND CHALLENGES FACED - Muslem; Hidayati; Maryam; Risna Dewi; Mauludi (RADJA PUBLIKA, 2025)
The problem in this study is the suboptimal empowerment of female melinjo emping artisans in Gampong Kandang, Kembang Tanjong District, Pidie Regency, which is characterized by limited access to capital, the use of traditional production technology, and marketing that is still dependent on collectors, resulting in low welfare improvements for female artisans. The focus of this study is directed at the empowerment of female melinjo emping artisans based on Hasdiansyah's community empowerment theory which includes the dimensions of education and training, access to capital, infrastructure, and entrepreneurship promotion, as well as obstacles faced in the empowerment process. This study aims to analyze the empowerment of female melinjo emping artisans in improving welfare and identify obstacles faced in its implementation. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation, with informants consisting of village government officials, related agencies, community leaders, and female artisans. The results of the study indicate that the empowerment of female melinjo emping artisans has been ongoing but is not optimal, which is characterized by unsustainable training and guidance, limited access to capital, inadequate production facilities, and product marketing that has not developed due to limited use of information technology. Key obstacles include limited knowledge, dominant domestic roles, low institutional participation, and unequal economic access. Therefore, women's empowerment requires a structured, planned, and sustainable approach through government support in providing access to capital, advanced training, strengthening business group institutions, and enhancing digital marketing to increase economic independence and family well-being.